Pengaruh Permainan Tradisional Engklek Terhadap Hasil Belajar Siswa Materi Pelajaran Matematika Kelas VI Di MI Hidayatus Shibyan Kemuning - Khoirum Mamnu’ah; Rahmat Rudianto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
Learning mathematics is learning that can train and foster logical, systematic, creative and consistent ways of thinking and being able to develop oneself in solving problems. But there are still many students who do not like mathematics because it is difficult and complicated which is always related to symbols, numbers, formulas, and calculations. Therefore the teacher must use methods or media that are fun for students. So that students do not get bored when studying mathematics and to get the desired learning outcomes. One of the methods used in learning mathematics is the traditional hopscotch game. This study aims to determine whether or not there is an influence of the traditional engklek game on student learning outcomes in mathematics subject matter for the flat shape chapter for class VI MI Hidayatus Shibyan Kemuning. This type of research is a quantitative experimental method with a Pre-Experimental Design that uses a one group pretest-posttest design approach consisting of pretest, treatment, and posttest. This research uses nonprobability sampling technique with saturated sampling method. The sample in this study were all students of Class VI MI Hidayatus Shibyan Kemuning. The results showed that an average value of 54.05 was obtained from student learning outcomes before the traditional hopscotch game. Then an average value of 74.25 was obtained from student learning outcomes after the traditional hopscotch game. Then supported by the results of nonparametric statistics marked Wilcoxon Signed Rank Test obtained Asymp.Sig (2-tailed) value of 0.00 <0.05 then Ho is rejected and Ha is accepted. Based on the results of this study, it can be stated that the traditional game of hopscotch has an effect on student learning outcomes in the subject matter of mathematics in the flat shape chapter for class VI MI Hidayatus Shibyan Kemuning.